When CLIL is for all: Improving learner motivation through peer-tutoring in Mathematics. (June 2022) - Martí Arnándiz, Otilia; Moliner, Lidon; Alegre, Francisco
Abstract: The obligatory provision of CLIL is raising concerns about the discouraging effects it may have. Yet little research so far has explored the impact of collaborative classroom methodologies on learners' motivation towards both content and language in integration. The present study sets out to examine the potential benefits of peer-tutoring in raising motivation towards CLIL in Mathematics for Compulsory Secondary Education. A pretest-posttest with control group design was adopted. Participants were 408 students from grades 7, 8 and 9 in a state-run secondary school based in the Valencian Community (Spain). Two factors were analyzed: intrinsic motivation (i.e. positive attitude and classroom enjoyment) and motivational force (i.e. confidence and anxiety). Eight focus groups provided qualitative data. Findings point to statistical significant increases for the experimental group in both factors but with moderate effect sizes. The peer-tutoring experience proves more positive for the younger participants (7 graders) and for enhancing males' intrinsic motivation and females' motivational force. The qualitative results obtained from the focus groups also suggest that these pedagogical practices may reduce students' anxiety, build their self-confidence and encourage more positive attitudes towards CLIL. Implementing peer-tutoring in CLIL, then, might improve students' motivation towards Mathematics through English. Highlights: Extrinsic and intrinsic motivation in CLIL through peer tutoring was examined. 408 students from grades 7, 8 and 9 in a state-run secondary school participated. Statistical significant increases for the experimental group were found. Moderate effect sizes were reported for both types of motivation. Analysis by ages and gender showed significant differences in the effects.